(untitled) (Jurnal Agribisnis dan Agrowisata, 2026)
The Development Strategy of Udayana University Faculty of Agriculture Experiment Garden As An Agricultural Education and Recreation. As an effort to advance and enhance the existence of the Udayana University Faculty of Agriculture Experiment Garden (KPFP), agro-tourism activities with the concept of agricultural education recreation (agroedutourism) are considered appropriate to be applied in the Faculty of Agriculture Experiment Garden (KPFP) of Udayana University. Therefore, this research is needed to analyze the strategy and potential in developing the Udayana University Faculty of Agriculture Experiment Garden as an agricultural education recreation (agroedutourism). Locations were determined using the deliberate method with qualitative quantitative descriptive analysis methods. Both internal and external factors illustrate the position of the Experimental Garden of the Faculty of Agriculture (KPFP) of Udayana University in the development of agricultural education recreation, currently at a high position. IFAS matrix value was obtained at 3.17 and EFAS matrix value was obtained at 3.09. illustrate that in developing agricultural education recreation (agroedutourism), the Experimental Garden of the Faculty of Agriculture (KPFP) of Udayana University has strong internal conditions and has a high ability to take advantage of opportunities and overcome threats from external parties.